Does in-Stream Video Advertising Work? Effects of Position and Congruence on Consumer Responses. Issue 5 (4th July 2022) - Freeman, Jason; Wei, Lewen; Yang, Hyun; Shen, Fuyuan
Abstract: The success of video streaming social networking sites (e.g., YouTube) is reliant upon savvy integration of advertising into massive amounts of user-generated content. These sites must weigh when, where, and how much advertising should be utilized to increase profit without causing irritation. This study examined two key variables related to streaming advertising (i.e., ad position and contextual congruence), and tested their impact on anger, perceptions of intrusiveness, and narrative engagement. Utilizing an online experiment ( N = 327), we found that mid-roll ads led to higher levels of perceived intrusiveness and anger than pre-roll ads. Anger and perceived intrusiveness were shown to significantly mediate the effect of mid-roll ad placements on ad and brand attitudes, with anger also mediating purchase intention. Though narrative engagement did not mediate the relationship between ad placement and resulting outcomes, we identified a sequential anger-narrative engagement mediating effect that shaped ad and brand outcomes. Theoretical and practical implications are discussed.